Gender, Sexual, and Racial Trouble: The Crossroads of North American Freemasonry in the Twenty-First Century - de los Reyes Heredia, Guillermo (Editorial de la Sede del Pacífico de la Universidad de Costa Rica, 2012)
This essay poses some questions on the current state of gender, race, and sexuality in American Freemasonry. The aim of this article is to shed light on this neglected topic and contribute to the growing and much needed discussion on gender, sexuality and Freemasonry. It is argued here that the discourses on tradition, masculinity, and antiquity have kept women, ethnic minorities, and openly homosexual men outside the lodge room. We will first discuss the racial aspect, focusing on Prince Hall Freemasonry. Furthermore, we will analyse the role that masculinity has played on Freemasonry and how the Masons have reacted to it. Then, we will briefly explore the role that women have played on Freemasonry and how they have been kept outside the Masonic main stream, along with other sexual minorities.